Cultura, cultura escolar y contenidos de enseñanza - José M. ESTEVE; Julio VERA; Soledad FRANCO; Amparo CIVILA (Ediciones Universidad de Salamanca, 2016)
After obtaining more than two hundred examinations utilizated in 36 primary schools with children 12 years old, an standard examination was made mixing questions of differents subjects. This examination was passed for a group of universitary students failing clearly. How is possible to considere as scholar failure the case of a 12 years old child, just having had no success in the same examination in wich universitary students neither had beeing able to answer? What is wrong, the elaboration of examinations for 12 years old children or the academic level of universitary students? Which are the criteria in order to select the contents of curriculum? Our article concludes the presence of proceedings in our schools based in traditions without no more justification: irrelevants contents, ellection of absurd questions in examinations, bias and conceptuals errors in explanation of subjects, etc.